1992
DOI: 10.1080/10408399209527588
|View full text |Cite
|
Sign up to set email alerts
|

Safety evaluation of olestra, a nonabsorbed, fatlike fat replacement

Abstract: Olestra is the mixture of the hexa-, hepta-, and octa-esters of sucrose with long-chain fatty acids from any edible oil. Its physical properties are comparable to those of triglycerides, but it is not digested by lipolytic enzymes or absorbed and therefore is noncaloric. Technically, it can replace fat in a wide variety of foods and can be used to make cooked, baked, and fried foods lower in fat and calories. A Food Additive Petition is under review by the FDA, which is comprised of results of extensive testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The nutritional composition of set meals used at the lunch (conditions A and B) and dinner (C and D) is set out in Table 2. Fat replacement was achieved by using SPE which is a mixture of hexa-, hepta-and octaesters of sucrose with edible long-chain fatty acids (Bergholz, 1992). SPE is not digested by pancreatic lipases (Drewnowksi, 1990).…”
Section: Design and Test Mealsmentioning
confidence: 99%
“…The nutritional composition of set meals used at the lunch (conditions A and B) and dinner (C and D) is set out in Table 2. Fat replacement was achieved by using SPE which is a mixture of hexa-, hepta-and octaesters of sucrose with edible long-chain fatty acids (Bergholz, 1992). SPE is not digested by pancreatic lipases (Drewnowksi, 1990).…”
Section: Design and Test Mealsmentioning
confidence: 99%
“…(11) In a study using rats and monkeys, accumulation of olestra in the liver, the primary target organ for absorbed olestra, was less than 3 × 10 −6 % of the total amount eaten (up to 9% of the diet) by rats over 24 months and less than 4 × 10 −5 % of the amount eaten (up to 8% of the diet) by monkeys over 29 months; instead, olestra was excreted in the feces. (13) Moreover, olestra was demonstrated as nontoxic, (14,15,16) nonreproductive toxic, (15) noncarcinogenic, (16,17) nonmutagenic and having no effect in chromosomal aberrations or DNA repair (18) in rats and mice. Eastwood and Allgood (19) found that olestra does not have any effect on the population of the intestinal microflora and their metabolic activities.…”
Section: Absorption and Metabolism Of Olestramentioning
confidence: 98%
“…Consequently, most published safety studies on fat replacers have been conducted with olestra. These studies address the potential for toxicity and the potential of olestra to affect the structure and function of the gastrointestinal tract and the effects it might have on digestion and absorption of drugs or other nutrients (e.g., fat-soluble vitamins and fat-soluble drugs) (29).…”
Section: Review Of Safety Literaturementioning
confidence: 99%